Close to the diffraction limit in high resolution ATR FTIR mapping: demonstration on micrometric multi-layered art systems. Issue 24 (23rd November 2017) - Bertasa, Moira; Possenti, Elena; Botteon, Alessandra; Conti, Claudia; Sansonetti, Antonio; Fontana, Raffaella; Striova, Jana; Sali, Diego
Abstract : This paper demonstrates the potentiality of high resolution micro-ATR-FTIR to reconstruct micrometric layers images. Abstract : This paper is aimed at demonstrating the potentiality of high resolution Attenuated Total Reflection Fourier Transform Infrared micro-mapping (micro-ATR-FTIR) to reconstruct the images of micrometric multi-layered systems. This method can be an effective analytical alternative when the layer thickness requires high lateral resolution, and fluorescence or thermal effects prevent the deployment of conventional analytical techniques such as micro-Raman spectroscopy. This study demonstrates the high micro-ATR-FTIR setup performances in terms of lateral resolution, spectral quality and chemical image contrast using a new laboratory instrument equipped with a single element detector. The method has been first validated on mock-ups and then successfully applied on cross-sectional samples from real artworks: Leonardo da Vinci's mural painting, characterised by a few micrometers thin sequence of organic and inorganic layers, and an outdoor marble statue, with a complex sequence of decay products on its surface. This study paves the way to a new investigation modality of micrometric systems, combining high lateral resolution with excellent spectral quality, essential in the field of Cultural Heritage as well as in the wider area of materials and forensic sciences.